Shorter outpatient wait-times for buprenorphine are associated with linkage to care post-hospital discharge. (1st July 2021) - Roy, Payel J.; Price, Ryan; Choi, Sugy; Weinstein, Zoe M.; Bernstein, Edward; Cunningham, Chinazo O.; Walley, Alexander Y.
Highlights: Addiction consult can improve buprenorphine treatment for hospitalized patients. Not every patient started on buprenorphine inpatient links to outpatient treatment. Clinics should engage with recently discharged patients with opioid use disorder. Abstract: Background: Inpatient addiction consult services (ACS) lower barriers to accessing medications for opioid use disorder (MOUD), however not every patient recommended for MOUD links to outpatient care. We hypothesized that fewer days between discharge date and outpatient appointment date was associated with improved linkage to buprenorphine treatment among patients evaluated by an ACS. Methods: We extracted appointment and demographic data from electronic medical records and conducted retrospective chart review of adults diagnosed with opioid use disorder (OUD) evaluated by an ACS in Boston, MA between July 2015 and August 2017. These patients were initiated on or recommended buprenorphine treatment on discharge and provided follow-up appointment at our hospital post-discharge. Multivariable logistic regression assessed whether arrival to the appointment post-discharge was associated with shorter wait-times (0−1 vs. 2+ days). Results: In total, 142 patients were included. Among patients who had wait-times of 0−1 day, 63 % arrived to their appointment compared to wait-times of 2 or more days (42 %). There were no significant differences between groups based on age, gender, distance of residence from the hospital, insurance status, co-occurring alcohol use disorder diagnosis, or discharge with buprenorphine prescription. After adjusting for covariates, patients with 0−1 day of wait-time had 2.6 times the odds of arriving to their appointment [95 % CI 1.3–5.5] compared to patients who had 2+ days of wait-time. Conclusion: For hospitalized patients with OUD evaluated for initiating MOUD, same- and next-day appointments are associated with increased odds of linkage to outpatient MOUD care post-discharge compared to waiting two or more days.